Many Paths to Many Clones: A Comparative Look at High-Throughput Cloning Methods - Marsischky, Gerald; LaBaer, Joshua (Genome Research, 2004)
The creation of genome-scale clone resources is a difficult and costly process, making it essential to maximize the efficiency of each step of clone creation. In this review, we compare the available commercial and open-source recombinational cloning methods with regard to their use in creating comprehensive open reading frame (ORF) clone collections with an emphasis on the properties requisite to use in a high-throughput setting. The most efficient strategy to the creation of ORF clone resources is to build a master clone collection that serves as a quality validated source for producing collections of expression clones. We examine the methods for recombinational cloning available for both the creation of master clones and their conversion into expression clones. Alternative approaches to creating clones involving mixing of cloning methods, including gap-repair cloning, are also explored.
10.1101/gr.2528804